Clever-1 positive macrophages in breast cancer - Mutka Minna; Virtakoivu Reetta; Joensuu Kristiina; Hollmén Maija; Heikkilä Päivi (SPRINGER, 2025)
Purpose: Common Lymphatic Endothelial and Vascular Endothelial Receptor 1 (Clever-1) is expressed by a subset of immunosuppressive macrophages and targeting the receptor with therapeutic antibodies has been shown to activate T-cell-mediated anti-cancer immunity. The aim of this research was to study Clever-1 expression in breast cancer. Specifically, how Clever-1 + macrophages correlate with clinicopathologic factors, Tumor Infiltrating Lymphocytes (TILs) and prognosis.
Methods: Tissue microarray blocks were made from 373 primary breast cancer operation specimens. Hematoxylin and Eosin (H&E-staining) and immunohistochemical staining with Clever-1, CD3, CD4 and CD8 antibodies were performed. Differences in quantities of Clever-1 + macrophages and TILs were analyzed. Clever-1 + cell numbers were correlated with 25-year follow-up survival data and with breast cancer clinicopathologic parameters.
Results: Low numbers of intratumoral Clever-1 + cells were found to be an independent adverse prognostic sign. Increased numbers of Clever-1 + cells were found in high grade tumors and hormone receptor negative tumors. Tumors that had higher amounts of Clever-1 + cells also tended to have higher amounts of TILs.
Conclusion: The association of intratumoral Clever-1 + macrophages with better prognosis might stem from the function of Clever as a scavenger receptor that modulates tumor stroma. The association of Clever-1 + macrophages with high number of TILs and better prognosis indicates that immunosuppression by M2 macrophages is not necessarily dampening adaptive immune responses but instead keeping them in control to avoid excess inflammation.